A simple formula for estimating the column ultimate load with effect of semi-rigid connections - Nassani, Dia Eddin; Chikho, Abdul Hakim; Nassanı, Dıa Eddın (KOREAN SOC STEEL CONSTRUCTION-KSSC, 2015)
Calculating the ultimate load of a framed column in sway structures involves, in the currently used design method, the calculation of the column effective length and utilizing the interaction formulae or tables. Therefore no allowance is made for the presence of semi-rigid connections in the currently used design method. In this paper, a new formula to calculate the column ultimate load is proposed using simple model to simulate the behavior of practical steel columns in sway structures. This formula takes into account the effect of semi-rigid connections, the column rotational end restraints and the ratio of the applied horizontal to vertical loads. Moreover, the proposed method has the advantage of allowing for the influence of the column end moments resulted from the presence of the externally applied loads. In order to verify the accuracy of the proposed formula, several examples are presented in which the column ultimate load have been calculated using the proposed formula and the well known computer program STAAD.Pro. Comparing the obtained results of the proposed method with those obtained from STAAD.Pro has shown good correlation and therefore the accuracy of the proposed method to predict the behavior of practical columns has been verified.
Keywords: connection; ultimate load; semi-rigid; steel beams; steel structures